Power Approaches to Policy-Making - Pokharel, Tej Raj (NCC Journal, 2019)
Society is the mixture of mass and elite group. Elite group of society remains in apex and forcefully take the space in decision making process, direct and instruct the mass as well as administrators and drag the power in their own hands. Elites manipulate mass opinion and sentiments. They rule masses of people. Elite theories introduce not only elites, but also new important subjects like power, and raise questions for example on oligarchic tendencies in democracy.